Speed, Agility, and Quickness (SAQ) training of the circuit system: How does it affect kick speed and agility of junior taekwondo athletes? - Akhmad, Imran; Nugraha, Tarsyad; Sembiring, Petrus (UIR Press, 2021)
The study is conducted based on a trainer's difficulty in improving the speed of kicks and agility of taekwondo junior athletes. This condition is a consideration for trainers to develop a proper and measurable cirquit SAQ training program to improve kick speed and agility for taekwondo novice athletes. This study aims to find out the effect of SAQ cirquit exercises with kick speed and agility. The research method used is an experimental method with equivalent time series design research design. The research is conducted for 6 weeks with a frequency of 1 week 3 exercises and consists of 3 series. Every 4 weeks it is done postest with design; (1) pre-test-treatment-portest stage 1, and (2) pre test-postest-postest stage 2. Data analysis technique uses t test with significance level 0.05. The results conclude that; (1) there is a significant influence between cirquit SAQ exercises on the kick speed of taekwondo junior athletes. (2) there is a significant influence between cirquit SAQ exercises on the agility of taekwondo junior athletes. From the results of this study, researchers expect that there will be recommendations to be used as further considerations for the future so that this study is more in-depth related to SAQ exercises, and hopefully this study can be a reference material for other researchers who want to research about the influence of SAQ exercises.